Предмет:
МатематикаАвтор:
анонимРешение задачи:
а) 5(с - 6) - 10 = 5с - 30 - 10 = 5с – 40 = 5(с – 8);
б)12 - 8(- 4 - х) = 12 + 32 + 8х = 44 + 8х = 4(11 – 2х);
в) - 6(х -7) + 14(t + 6) = - 6х + 42 + 14t + 84 = 14t – 6х + 126 = 2(7t – 3х + 63);
г) 32 - (х - у) = 32 – х + у;
д) - (-13х - 2t - 7у) + 5 = 13х + 2t + 7у;
е) -3,5 - (- х - 3,5) = - 3,5 + х + 3,5 = х;
ж) - (- с - у) + (с - t) = с + у + с – t = 2c + e – t;
з) 6(2 - 3х) – (5 + х) - 4(3х - 2) = 12 – 18х – 5 – х – 12х + 8 = 15 – 31х.
Автор:
harrietДобавить свой ответ
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
ЛитератураАвтор:
анонимОтветов:
Смотреть
Предмет:
ЛитератураАвтор:
анонимОтветов:
Смотреть